PEMANFAATAN LIMBAH SAYURAN PASAR SEBAGAI PAKAN ALTERNATIFDOMBA DI JEMBER - Sukadi Sukadi; Rina Rohmawati; Adzkiyak Adzkiyak (LPPM IKIP Jember, 2018)
Empowerment and mentoring activities for alternative feed making from market vegetable waste in traditional or conventional goat breeders is an attempt to make the farmers groups to be empowered in goat farm business activities undertaken. Science Activities for the community (IbM) Utilization of Market Vegetables Waste as Alternative Livestock Feed. The potential of many resources in rural areas in Jember Regency is a market waste disposal site in the form of vegetables. If this can be utilized properly it will greatly assist traditional farmers in the fulfillment of goat feed especially in the dry season. The difficulty of renerization feed that can only be fulfilled in the rainy season can be overcome by the manufacture of alternative feed from the waste materials of the vegetable market. The cost of feed in goat breeding activities reaches 60 percent of operational costs, because it must be met every day. This condition will increase if coming dry season. Goat farmers will have difficulty in feeding goat farms managed by Goat Farming Group (KUB) in Karangkedawung Village, Mumbulsari District and Kemuningsari Lor Village, Jenggawah Subdistrict, Jember Regency. This activity aims to assist traditional goat breeders in reducing feed production costs by introducing a touch of technology for processing vegetables and fruits waste as feedstock for making vermentation feed. Method of empowerment activity is participative method, that is involving target group starting from planning, implementation until monitoring and evaluation. The goal to be achieved in this activity is to increase the economic benefits of traditional goat breeders so as to increase the family's economic income. In addition, this empowerment activity is also able to encourage the development and independence of business groups with traditional goat farmers in Jember district.